Efficacy of oral metronomic chemotherapy in the management of head and neck squamous cell carcinoma—a systematic review - Segin Chandran, Aardra Binithadas; Pandiar, Deepak; Krishnan, Reshma Poothakulath; Gopinath, Divya (Frontiers in Oral Health, 2025)
BackgroundHead and neck squamous cell carcinoma (HNSCC) is a group of heterogeneous malignancies and constitutes one of the most prevalent forms of cancer. Oral metronomic chemotherapy (OMCT) is a treatment in which low doses of anticancer drugs are given at regular intervals over a long time, with many advantages over conventional therapies, particularly in nations with high cancer burden. The present systematic review aimed to evaluate the efficacy of OMCT in the management of HNSCC in comparison to other standard chemotherapy regimens. Methodology: The review was registered in the Prospero database (CRD42023426000). An electronic search was conducted using PubMed, Scopus, Web of Science and Google Scholar databases. Articles in which OMCT was used to treat HNSCC were included for systematic review, and the survival and response rates were analyzed.ResultsTwenty-four eligible articles were included for evaluation, which revealed that administration of OMCT produced higher survival and response rates in subjects compared to standard chemotherapy.ConclusionThe evidence from the included studies supports that oral metronomic chemotherapy is substantially more effective as compared to standard chemotherapy regimens in squamous cell carcinomas of the head and neck.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42023426000, identifier (CRD42023426000).